Strategic management in tourism - Moutinho, Luiz (CABI Publishing, 2000)
"This book contains coverage and analytical discussion of key areas of contemporary tourism management: evaluation of the most important global trends in tourism, analysis of the impact of crucial environmental issues and their implications and the major factors affecting international tourism. Furthermore, the book covers tourism marketing issues and other areas of functional management as well as strategic planning and tourism. The aim of this advanced textbook is to provide a vision of integrated management which will benefit students in their future careers in the areas of business studies, tourism and planning."--Jacket.